2021
DOI: 10.1111/all.15002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular definition of severe acute respiratory syndrome coronavirus 2 receptor‐binding domain mutations: Receptor affinity versus neutralization of receptor interaction

Abstract: Background Several new variants of SARS‐CoV‐2 have emerged since fall 2020 which have multiple mutations in the receptor‐binding domain (RBD) of the spike protein. It is unclear which mutations affect receptor affinity versus immune recognition. Methods We produced wild type RBD, RBD with single mutations (E484K, K417N, or N501Y) or with all three mutations combined and tested their binding to ACE2 by biolayer interferometry (BLI). The ability of convalescent sera to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…BLI sensorgrams illustrating the interaction between ACE2 and (A) wild-type RBD (RBD WT ); (B) E484K single-mutant RBD (RBD E484K ); (C) L452R/E484Q double-mutant RBD (RBD L452R/E484Q ; and (D)) N440 singlemutant RBD (RBD N440K ) Note: *RBD WT =Receptor-Binding Domain wild type, *RBD L452R/E484Q = Receptor-Binding Domain L452R, E484Q mutations, *RBD E484K = Receptor-Binding Domain E484K mutation, *RBD N440K = Receptor-Binding Domain N440Kmutation.TA B L E 1 Kinetic parameters for the RBD-ACE2 interaction calculated by BLIThis result is not surprising, as mutation E484K has already been shown to evade immunity in the context of variants B.1.351 and P.1 12,13,16. Likewise point mutations conferred by L452R or E484Q alone have been shown to reduce sensitivity to antibodies elicited by BNT162b2 vaccine 17.…”
mentioning
confidence: 89%
“…BLI sensorgrams illustrating the interaction between ACE2 and (A) wild-type RBD (RBD WT ); (B) E484K single-mutant RBD (RBD E484K ); (C) L452R/E484Q double-mutant RBD (RBD L452R/E484Q ; and (D)) N440 singlemutant RBD (RBD N440K ) Note: *RBD WT =Receptor-Binding Domain wild type, *RBD L452R/E484Q = Receptor-Binding Domain L452R, E484Q mutations, *RBD E484K = Receptor-Binding Domain E484K mutation, *RBD N440K = Receptor-Binding Domain N440Kmutation.TA B L E 1 Kinetic parameters for the RBD-ACE2 interaction calculated by BLIThis result is not surprising, as mutation E484K has already been shown to evade immunity in the context of variants B.1.351 and P.1 12,13,16. Likewise point mutations conferred by L452R or E484Q alone have been shown to reduce sensitivity to antibodies elicited by BNT162b2 vaccine 17.…”
mentioning
confidence: 89%
“…Subsequent reports have demonstrated that increased transmissibility and immune escape are linked to these lineages, which are defined by spike receptor binding domain (RBD) mutations, including N501Y, K417N/T, L452R, and E484K. Notably, the E484K and L452R mutations in RBD had previously been demonstrated to confer immune escape in cell culture selection experiments 5 , which is consistent with their increasing prevalence 6,7 , possibly due to increased viral fitness 8,9 . Therefore, vigilant monitoring of circulating strains for these mutations is of critical importance for potentially preventing their spread.…”
mentioning
confidence: 68%
“…In addition to strains carrying L452R individually, variant strains carrying a combination of L452R + N501Y (3/117, 2.6%) were also identified. The N501Y mutation confers higher affinity for the ACE2 receptor and is present in several variants of concern (alpha, beta, gamma) while L452R is a signature escape mutation found in the delta and epsilon lineages that also increases infectivity 4,8,9,15,16 . The combination of both of these mutations in one strain is of concern for potential rapid spread of an immune escape variant.…”
mentioning
confidence: 99%
“…Contrary were the results with the E484K mutation, where no enhanced binding to ACE2 was shown but much lower recognition by convalescent sera. Triple mutant RBD (K417N/E484K/N501Y) exhibited both features: stronger affinity to ACE2 and much lower detection by convalescent sera 33 . Since vaccines optimally mediate protection for many years, vaccine induced Abs should therefore be able to recognize new virus variants as well.…”
Section: Discussionmentioning
confidence: 99%